External shocks, exchange rate adjustments, and income distribution in Egypt - Raouf, Mariam; Ghaly, Sherine Boshra; Wiebelt, Manfred; Elhamalawy, Fatma (2024)
This study examines the complex dynamics of the Egyptian economy in response to external shocks and currency devaluation. Applying a SAM-based CGE model, the research focuses on the economic linkages between production sectors, households, government and the rest of the world, on resource competition on markets for production factors and goods, and on macroeconomic constraints in the government budget, savings and investment, and foreign exchange revenues. Key findings reveal the substantial impact of differential domestic inflation (45%) and the challenges posed by limited foreign exchange inflows (32%) and eroded export competitiveness (19%). External shocks, including the COVID-19 pandemic and geopolitical events, yield nuanced impacts on GDP, employment, household consumption, and inequality. Sectoral analyses highlight varied effects on export-oriented and non-tradable industries. As Egypt grapples with global challenges, the study emphasizes the need for targeted policies balancing export competitiveness, foreign savings, and domestic stability. The findings contribute practical insights for policymakers navigating the complexities of a dynamic global economy.